FAILURE ANALYSIS IN METALLIC MATERIALS: TOOLS, STRATEGIES, AND TECHNOLOGICAL IMPACT (Editora Impacto Científico, 2025)
This chapter provides a technical-conceptual review of failure analysis methodologies applied to metals, focusing on their structure, stages, and supporting tools. It discusses key approaches established in the literature, from classical models by Colangelo and Heiser to recent contributions by Aidy Ali, highlighting their differences in depth, detail, and applicability. The chapter systematizes the fundamental stages of analysis, including the investigation of the component’s service history, macro- and microfractographic examinations, chemical microanalyses, metallography, and physical or computational simulations. It also emphasizes the role of quality management tools, such as the 5 Whys, Ishikawa Diagram, FMEA, and FTA, as essential complements to technical investigations and preventive measures. By integrating scientific, practical, and managerial foundations, the chapter underlines that failure analysis is a strategic instrument for technological and industrial advancement, contributing to enhanced reliability, operational safety, and process sustainability.DOI: https://doi.org/10.56238/edimpacto2025.090-052